Defect driven tailoring of colossal dielectricity of Reduced Graphene Oxide. (February 2016) - Sarkar, S.; Mondal, A.; Dey, K.; Ray, R.
Graphical abstract: Highlights: Reduced graphene oxides (RGO) are prepared by two chemical routes. Defects in RGO are characterized by Raman, FTIR and XPS studies. Defects tailor colossal dielectricity in RGO. Abstract: Reduced graphene oxide (RGO) is prepared in two different chemical routes where reduction of graphene oxide is performed by hydrazine hydrate and through high pressure in hydrothermal reactor. Samples are characterized by X-ray powdered diffraction (XRD), thermo gravimetric analysis (TGA), field emission scanning electron microscopy (FESEM) and tunneling electron microscopy (TEM). Types of defects are probed by Raman, FTIR spectroscopy and X-ray photoelectron spectroscopy (XPS). UV–vis absorption reveals different optical band gaps of the two RGOs. Conductivity mechanism is studied through I – V measurements displaying different characteristic features which are addressed due to the presence of defects appeared in different synthesis. Significantly high value (∼10 4 ) of dielectric permittivity at 10 MHz is attractive for technological application which could be tuned by the defects present in RGO.